DRIVING PROGRESS TOGETHER: EMBRACING INCLUSIVE DEVELOPMENT FOR INFRASTRUCTURE IN EAST INDONESIA - Ramadhan, Rifqi Dhia; Fauzi, Fadhli Zul (ipdn, 2023)
This research aims to look at efforts of inclusive development in eastern Indonesia and what challenges occur in its development. Researchers see that inclusive and sustainable infrastructure development can be one of the answers or efforts to solve development problems in eastern Indonesia. Recent literature about infrastructure development in East Indonesia is used in this research. We grouping it with the core of SDG’s to see is the development in Indonesia is paying attention to inclusive and sustainable aspect or not. This research found that inclusive development could have a significant impact on Eastern Indonesia in the future, where community participation could actually assist in improving other aspects such as the economy and environmental sustainability. However, some challenges such as awareness of education and gender equality still need to be addressed, while some literatures consider this to be the most important or common issue in infrastructure development, especially in eastern Indonesia. Keywords: Inclusive Development, Infrastructure, Economic Growth, East Indonesia